Animal experimental models of ischemic wounds - A review of literature - Lovasova, Veronika; Bem, Robert; Chlupac, Jaroslav; Dubsky, Michal; Husakova, Jitka; Nemcova, Andrea; Fronek, Jiri (Wound repair and regeneration, 2022)
Critical limb ischemia is a serious form of peripheral arterial disease (PAD). The consequences of lower limb ischemia are pain, claudication and chronic non-healing wounds. Patients with diabetes are especially at a high risk for developing non-healing ulcers. The most serious complication is major amputation. For this reason, there is a significant medical requirement to develop new therapies in order to prevent the progression of PAD. For research purposes, it is crucial to find an appropriate model of chronic ischemia to explore the processes of wound healing. According to recently acquired information, rodents are currently the most commonly used animals in these types of studies. The main advantage of using small animals is the low financial cost due to the relatively small demand for food, water and living space. The disadvantage is their anatomy, which is different from that of humans. Larger animals have a more human-like anatomy and physiology, but they require more expense and space for housing. A bipedicle skin flap and its modifications are popular models for ischemic wounds. In order to secure healing through re-epithelisation, as opposed to contraction in rodents, there is a need to remove the panniculus carnosus muscle. Wounds in other experimental animals heal primarily through re-epithelisation. The application of a silicone mesh underneath the flap prevents vascular regrowth in ischemic tissue. There is an ongoing effort to create in vivo diabetic models for chronic ulcer research. This work presents an overview of existing animal models of ischemic wounds.
Keywords: Animals; teoretické modely; diabetic ulcers; Peripheral Arterial Disease; amputace; Wound Healing; Amputation, Surgical; diabetes mellitus; lidé; animal experimental model; in vivo model; Models, Animal; onemocnění periferních arterií; hojení ran; Ischemia; ischemie; zvířata; ischemic wound; Models, Theoretical; modely u zvířat; Humans